2000
DOI: 10.1046/j.1525-1497.2000.03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of general internal medicine teaching units

Abstract: OBJECTIVE:To identify and describe general internal medicine teaching units and their educational activities. DESIGN:A cross-sectional mailed survey of heads of general internal medicine teaching units affiliated with U.S. internal medicine training programs who responded between December 1996 and December 1997. MEASUREMENTS AND MAIN RESULTS:Responses were received from 249 (61%) of 409 eligible programs. Responding and nonresponding programs were similar in terms of university affiliation, geographic region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For example, we assumed that respondents would be familiar with terms such as “core, full- and part-time faculty” but it is possible that providing the ACGME’s explicit definition of these terms [ 23 ] would have provided more accurate answers. In addition, the authors did not take into account the contribution made by volunteer faculty; a 2000 study of internal medicine residency training programs suggest that unpaid faculty provide a significant teaching contribution [ 24 ]. It must be recognized that this study is a snapshot and the results clearly indicating that the landscape of resident education is fluid.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we assumed that respondents would be familiar with terms such as “core, full- and part-time faculty” but it is possible that providing the ACGME’s explicit definition of these terms [ 23 ] would have provided more accurate answers. In addition, the authors did not take into account the contribution made by volunteer faculty; a 2000 study of internal medicine residency training programs suggest that unpaid faculty provide a significant teaching contribution [ 24 ]. It must be recognized that this study is a snapshot and the results clearly indicating that the landscape of resident education is fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this is a study of faculty at academic residency programs affiliated with medical schools; therefore, their views may not reflect those of faculty at community-based programs where a substantial portion of medical student education occurs. 36 Third, although we demonstrate some degree of content validity for survey items based on our iterative process of survey development among teaching faculty, we do not provide any measure of criterion validity for survey items. Fourth, we did not collect data on teaching methods (e.g., didactic vs. bedside), and therefore, we can not examine differences in KCF views based on this variable.…”
Section: Discussionmentioning
confidence: 67%
“…In 1 collaboration between an internal medicine residency program and a federally qualified health center, resident and patient satisfaction improved, but the grant did not offset the hospital's financial investment 67 . A national survey of general internal medicine teaching units showed that general internist volunteers outside of the university environment do a significant portion of internal medicine teaching 68 …”
Section: Resultsmentioning
confidence: 99%